Stromal categorization in early oral tongue cancer - Almangush Alhadi; Bello Ibrahim O.; Ibrahim O. Heikkinen Ibrahim O.; Hagström Jaana; Haglund Caj; Kowalski Luiz Paulo; Nieminen Pentti; Coletta Ricardo D.; Mäkitie Antti A.; Salo Tuula; Leivo Ilmo (SPRINGER, 2022)
Stromal categorization has been used to classify many epithelial cancer types. We assessed the desmoplastic reaction and compared its significance with other stromal characteristics in early (cT1-2N0) oral tongue squamous cell carcinoma (OTSCC). In this multi-institutional study, we included 308 cases treated for early OTSCC at five Finnish university hospitals or at the A.C. Camargo Cancer Center in Sao Paulo, Brazil. The desmoplastic reaction was classified as immature, intermediate, or mature based on the amount of hyalinized keloid-like collagen and myxoid stroma. We compared the prognostic value of the desmoplastic reaction with a stromal grading system based on tumor-stroma ratio and stromal tumor-infiltrating lymphocytes. We found that a high amount of stroma with a weak infiltration of lymphocytes was associated statistically significantly with a worse disease-free survival with a hazard ratio (HR) of 2.68 (95% CI 1.26-5.69), worse overall survival (HR 2.95, 95% CI 1.69-5.15), and poor disease-specific survival (HR 2.66, 95% CI 1.11-6.33). Tumors having a high amount of stroma with a weak infiltration of lymphocytes were also significantly associated with a high rate of local recurrence (HR 4.13, 95% CI 1.67-10.24), but no significant association was found with lymph node metastasis (HR 1.27, 95% CI 0.37-4.35). Categorization of the stroma based on desmoplastic reaction (immature, intermediate, mature) showed a low prognostic value for early OTSCC in all survival analyses (P> 0.05). In conclusion, categorization of the stroma based on the amount of stroma and its infiltrating lymphocytes shows clinical relevance in early OTSCC superior to categorization based on the maturity of stroma.